2020
DOI: 10.3390/ijms21197418
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptome Analysis, Conserved Regulatory Elements and Associated Transcription Factors Related to Accumulation of Fusariotoxins in Grain of Rye (Secale cereale L.) Hybrids

Abstract: Detoxification of fusariotoxin is a type V Fusarium head blight (FHB) resistance and is considered a component of type II resistance, which is related to the spread of infection within spikes. Understanding this type of resistance is vital for FHB resistance, but to date, nothing is known about candidate genes that confer this resistance in rye due to scarce genomic resources. In this study, we generated a transcriptomic resource. The molecular response was mined through a comprehensive transcriptomic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…KEGG enrichment analysis counted only genes that were significantly differentially expressed, while GSEA, from the perspective of the enrichment of gene sets, was not limited to the DEGs, so it was theoretically easier to identify some genes that had small changes in expression but played a role in biological functions [37]. GSEA has been widely used for gene functional analysis in plants [38]. In this study, both KEGG enrichment analysis and GSEA revealed the disease resistance pathways of II-9-3.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis counted only genes that were significantly differentially expressed, while GSEA, from the perspective of the enrichment of gene sets, was not limited to the DEGs, so it was theoretically easier to identify some genes that had small changes in expression but played a role in biological functions [37]. GSEA has been widely used for gene functional analysis in plants [38]. In this study, both KEGG enrichment analysis and GSEA revealed the disease resistance pathways of II-9-3.…”
Section: Discussionmentioning
confidence: 99%
“…FHB is caused primarily by Fusarium graminearum infection, leading to the accumulation of several mycotoxins in grain such as predominantly deoxynivalenol (DON), nivalenol (NIV), and zearalenone (ZEN) which make grain unsuitable for human consumption and livestock feed [112]. Low mycotoxin accumulation is Type III FHB resistance [4], which is also considered as a component of Type II resistance because it commonly reduces the spread of disease [113]. Boutigny et al [114] further proposed classification of Type III resistance into two types: resistance to trichothecene accumulation by metabolic transformation of the toxin and resistance via inhibition of trichothecene biosynthesis.…”
Section: Type III Resistancementioning
confidence: 99%
“…The objective of this study was to elucidate how M7SB41 enhanced host plants PM resistance. Comprehensive transcriptome analysis can provide an ideal platform to investigate the genome-wide differentiations underlying the differently physiological traits, as well as to uncover complex signaling pathways activated in response to pathogen infection [ 25 ]. Therefore, to elucidate the mechanisms involved in host plants PM resistance induced by M7SB41, the differentially expressed genes between E+ and E− plants were studied by transcriptomic techniques.…”
Section: Introductionmentioning
confidence: 99%